Variations in the emission of polymethylene-vaulted trans-bis(salicylaldiminato)platinum(II) complexes incorporating methoxy functionalities with linkage length and substitution position. (25th September 2015) - Komiya, Naruyoshi; Okada, Minoru; Inoue, Ryo; Kawamorita, Soichiro; Naota, Takeshi
Graphical abstract: Polymethylene-vaulted trans -bis(salicylaldiminato)platinum(II) complexes bearing methoxy functionalities exhibit highly regular variations in emission wavelengths with changes in both the substituent position and the linkage length in the glassy state in 2-MeTHF. Abstract: A series of methoxy-substituted trans -bis(salicylaldiminato)platinum(II) complexes (1b, 2b, 3b, 4a –d, 5a –d and6a –d ) incorporating octa-, nona-, deca-, undeca-, dodeca- and tridecamethylene bridges has been synthesized and their unique structure-dependencies in the solution state emission are described. Methoxy-substitution on the aromatic rings was found to improve the emission quantum efficiency in the glassy state in 2-MeTHF at 77 K. Chromogenic control over a range of 70 nm was demonstrated, with the 3-, 4-, 5- and 6-methoxy substitutions giving yellow, green, orange and yellow-green emissions, respectively. These complexes exhibited obvious linker-dependent emission chromism under the same conditions, such that a very regular hypsochromic shift from yellow to green was observed upon increasing the linker length.